Prosocial and antisocial behavior in sport: the roles of coach’s behavior and moral identity among youth athletes / Fariha Mohammad Fazilah - Mohammad Fazilah, Fariha (2024)
Prosocial and antisocial behaviors in sports are important topics to consider, as they can have a significant impact on both the individual athlete and the team. Studies have shown that coaches’ behavior and moral identity can influence athletes’ prosocial and antisocial behaviors, potentially affecting their preparation for competition. Coaches who provide autonomy support by allowing players more freedom of choice during practice or providing positive feedback may foster prosocial behavior among their athletes. Additionally, those with stronger moral identities tend to be more likely to engage in prosocial behavior than those without such identities. The study was an important yet understudied area. As such, it is critical to understand how coach behavior impacts athlete moral identity and performance. To fill the gap, the relationship, and differences of prosocial and antisocial behaviors in gender (male and female) and sport cagegories (team and individual sports) among youth athletes was conducted. This study used Pearson Correlation to investigate the relationship and Independent t-Test to measure the differences among the variables. The respondents in this study included 240 athletes in the youth category that consists of gender with males and females and sport categories with individual and team sports. The results showed that when coaches provided autonomy support or positive feedback it increased the likelihood of engaging in prosocial behavior while decreasing instances of antisocial behaviors overall across all participants regardless of gender differences or other demographic factors studied. The findings from this study suggest that if coaches strive to create environments where there is greater emphasis placed on developing strong morals through providing meaningful activities which allow for autonomy then we will see an increase in the number of individuals engaging pro social behavior within a sport context for both youth athletes and adults alike. Besides the immediate benefits for athletes and coaches, this form of study would provide advantages and potential to assist sports organizations such as the National Sports Council (MSN) and the National Sports Institute (ISN) in sports development. Sports psychology can provide insight into how best practices are being implemented within a team or organization, which could lead to more successful outcomes in training programs or competitions.